Flowers growing in the shadow stories of the second generation born after the Holocaust in Southwest Transdanubia : an unconventional review of Iván Zádori's "Második" monograph on Judaica culture and history - Nemeskéri Zsolt; Zádori Iván; Nagy Gábor Dániel (Belvedere Meridionale Szeged, 2025)
Iván Zádori’s book traces the life‐histories and memories of nearly sixty members of Southwest Transdanubia’s Jewish second generation—those born between 1945 and 1965 to Holocaust survivors. Using an oral‐history approach, the book reveals how these “children of survivors” negotiated Jewish identity, community life, and the legacies of trauma in postwar rural Hungary. Spanning childhood through to the present, Zádori interweaves personal narratives with regional history, highlighting both the singularity of Transdanubian experience and its resonance with broader debates on memory, identity, and intergenerational trauma. This review situates Második within national and international Holocaust scholarship, underscoring its methodological rigor, narrative richness, and contribution to understanding how memory and identity are co‐constructed across generations.
Keywords: Bölcsészettudományok; Történettudomány és régészet